Outpatient Primary Care Practitioner Access: Gender-Based Preferences - Saira J. Khan; Kenneth G. Poole; Juliana M. Kling; Gretchen Taylor (Mary Ann Liebert, 2022)
Background: Primary care practices are evolving under the pressure of modern-day challenges, with some clinics now introducing the choice of new nontraditional care models designed to maximize patients' needs with practitioner efficiency. These changes include team models consisting of advanced practitioners and physicians, as well as new care delivery formats such as virtual care. With a growing number of options for care, it is unclear whether patients' gender affects their visit preferences; therefore, we surveyed patients presenting to an outpatient internal medicine clinic in Arizona to understand how practice variations impact patient satisfaction of their primary care. Methods: Patients seen in an outpatient internal medicine clinic were surveyed. Multivariable models adjusting for age, marital status, education level, and income were used to evaluate gender-based care preferences. Results: Of 796 total participants (446 women, 350 men), women were more likely to prefer continuity of care with the same health care practitioner (90.2% women vs. 85.0% men, p?=?0.028) and allied health staff (AHS) (36.3% women vs. 28.0% men, p?=?0.0031) over convenience of appointment or quicker response time than men. However, after multivariable analysis, no statistically significant relationships remained. Discussion: Women favored both continuity of care with the same health care provider and AHS over faster access to primary care. A large majority of men had similar preferences for continuity of care. To provide the highest level of care with greatest patient satisfaction, understanding individual preferences for care delivery will be important.